Expanding AB-PMJAY For the Elderly: A Policy Shift Toward Universal Health Coverage in India - Sankar G, Kiruba; Mahendran, Rajalakshmi (National Journal of Community Medicine, 2025)
Ayushman Bharat Pradhan Mantri Jan Arogya Yojana (AB-PMJAY) is India's flagship health insurance scheme with the aim of Universal Health Coverage (UHC). With its recent expansion to all senior citizens above the age of 70, the scheme will have a greater impact on elderly health care and financial security. This review examines the effect of AB-PMJAY on access to healthcare, catastrophic health expenditure (CHE), and the infrastructure for geriatric care in India. The elderly population normally suffers from not only a high burden of non-communicable diseases but also several chronic health issues along with financial instability arising from low-income sources. The pool of reserves traditionally used to provide up to ₹5 lakh per person is expected to reduce out-of-pocket health expenses, increased hospital utilization, and improves overall health outcomes; however, issues relating to access, enrolment difficulties, lack of hospital infrastructure, and financial sustainability still linger. For policymakers, recommendations must be made in relation to improving enrolment processes, strengthening geriatric services, and being on guard against fraud, all in an effort to ensure the effectiveness of the scheme. Targeting these will be critical in enabling equitable access to healthcare and financial protection for the rapidly growing elderly population in India.